Evaluación en el proceso educativo - Seminario Méndez, Liliana (2011)
This research aims to highlight the importance of the educational process evaluation and to explain sorne evaluation tools applicable tothecareer of Lawin order that our students externalize their personality strengthen their abilities and become successful professional lawyers.